Common fixed points for alpha-psi-phi-contractions in generalized metric spaces - La Rosa, Vincenzo; Vetro, Pasquale (Nonlinear Analysis: Modelling and Control, 2014)
We establish some common fixed point theorems for mappings satisfying an α-ψ-ϕ-contractive condition in generalized metric spaces. Presented theorems extend and generalize manyexisting results in the literature.Erratum to “Common fixed points for α-ψ-φ-contractions in generalized metric spaces”In Example 1 of our paper [V. La Rosa, P. Vetro, Common fixed points for α-ψ-ϕ-contractions in generalized metric spaces, Nonlinear Anal. Model. Control, 19(1):43–54, 2014] a generalized metric has been assumed. Nevertheless some mistakes have appeared in the statement. The aim of this note is to correct this situation.
Keywords: generalized metric space; α-ψ-ϕ-contractive condition; contraction of integral type; fixed point; common fixed point